2016
DOI: 10.1136/tobaccocontrol-2016-053245
|View full text |Cite
|
Sign up to set email alerts
|

Hazards of cigarettes, smokeless tobacco and waterpipe in a Middle Eastern Population: a Cohort Study of 50 000 individuals from Iran

Abstract: Background There is limited information about the hazards of cigarettes, smokeless tobacco, and waterpipe in the Middle East. The aim of this study was to determine the association between different types of tobacco use and earlier death in the Golestan Cohort Study. Methods The Study includes 50,045 adults (aged 40–75) from northeastern Iran. The baseline questionnaire (2004–2008) assessed information about use of cigarettes, chewing tobacco (nass), and waterpipe. To assess the use of each type of tobacco c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 50 publications
1
37
0
Order By: Relevance
“…associated with about 90% higher risk of ESCC. Since in this study cigarette smoking prevalence was relatively low (particularly in women) and alcohol consumption was negligible, 20 there would be minimal residual confounding from smoking and alcohol, which could be a problem in other studies. Only two prospective cohort studies have previously examined the association between hot tea drinking and esophageal cancer.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…associated with about 90% higher risk of ESCC. Since in this study cigarette smoking prevalence was relatively low (particularly in women) and alcohol consumption was negligible, 20 there would be minimal residual confounding from smoking and alcohol, which could be a problem in other studies. Only two prospective cohort studies have previously examined the association between hot tea drinking and esophageal cancer.…”
Section: Discussionmentioning
confidence: 83%
“…In analysis of the combined effects of measured temperature and amount, drinking 700 mL/day tea or more at ≥60°C was associated with about 90% higher risk of ESCC. Since in this study cigarette smoking prevalence was relatively low (particularly in women) and alcohol consumption was negligible, there would be minimal residual confounding from smoking and alcohol, which could be a problem in other studies.…”
Section: Discussionmentioning
confidence: 85%
“…Studies reported the tobacco, inappropriate nutritional regimen, Body Mass Index, occupational dangers, and weather contamination as the cancer determinants in East-Mediterranean region [26][27]. The lung cancer was reported as the third cause of mortality in East-Mediterranean region in which tobacco usage was indicated as the main risk factor of it [28][29]. Inappropriate life style and physical inactivity were reported as the main causes of colorectal cancer [30].…”
Section: Discussionmentioning
confidence: 99%
“…A similar study in Middle Eastern Populations including 50,000 cohort members provided information on the association of cancer mortality with cumulative lifetime water‐pipe use. Water‐pipes were associated with the risk of earlier death . The study on esophageal squamous cell carcinoma (702 cases) in Kashmir, India established an association with water‐pipe smoking .…”
Section: Cancer Risks Associated With Smokingmentioning
confidence: 99%